2006
DOI: 10.1021/jp060029a
|View full text |Cite
|
Sign up to set email alerts
|

Stable Gas-Phase Radical Cations of Dimeric Tryptophan and Tyrosine Derivatives

Abstract: Stable radical cations of dimeric amino acid derivatives of tryptophan and tyrosine were generated by collision-induced dissociation of [Cu(II)(diethylenetriamine)(amino acid derivative)2]*2+. The yields of the dimer radical cations were dependent on both the auxiliary ligand and the tryptophan or tyrosine derivatives used. Amino acid derivatives with an unmodified carboxylic acid group did not generate dimer radical cations. For the amino acid derivatives Ac-Trp-OMe and Ac-Trp-NH2 (Ac is N-acetyl; OMe and NH2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…In parallel with the formation of P +• (Equation ), CID of the ternary complexes can also lead to a variety of other competitive reaction pathways. The other pathways include dissociative proton transfer to the peptide (Equation ), dissociative proton abstraction from the peptide (Equation ), and peptide fragmentation (Equation ) (Chu, Lam, & Siu, ; Ke et al, ; Hopkinson, ). [normalMn+(L)P]n+[normalMn+(L)](n1)++normalP+ [normalMn+(L)P]n+[normalMn+(LH)](n1)++[P+H]+ [normalMn+(L)P]n+[normalMn+(PH)](n1)++[L+H]+ [normalMn+(L)P]n+[normalM(n1)(L)(Pbn)](…”
Section: Formation and Migration Of A Radical Sitementioning
confidence: 99%
See 2 more Smart Citations
“…In parallel with the formation of P +• (Equation ), CID of the ternary complexes can also lead to a variety of other competitive reaction pathways. The other pathways include dissociative proton transfer to the peptide (Equation ), dissociative proton abstraction from the peptide (Equation ), and peptide fragmentation (Equation ) (Chu, Lam, & Siu, ; Ke et al, ; Hopkinson, ). [normalMn+(L)P]n+[normalMn+(L)](n1)++normalP+ [normalMn+(L)P]n+[normalMn+(LH)](n1)++[P+H]+ [normalMn+(L)P]n+[normalMn+(PH)](n1)++[L+H]+ [normalMn+(L)P]n+[normalM(n1)(L)(Pbn)](…”
Section: Formation and Migration Of A Radical Sitementioning
confidence: 99%
“…In parallel with the formation of P þ• (Equation 1), CID of the ternary complexes can also lead to a variety of other competitive reaction pathways. The other pathways include dissociative proton transfer to the peptide (Equation 2), dissociative proton abstraction from the peptide (Equation 3), and peptide fragmentation (Equation 4) (Chu, Lam, & Siu, 2005;Ke et al, 2006;Hopkinson, 2009).…”
Section: A Cid Of Ternary Metal Complexes With Peptide and Auxiliarymentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-complex electron transfer in ternary Cu (II) complexes has also been used to generate doubly charged radicals of the [peptide] 2þ. type , amino acid cation radicals (Ke et al, 2006;Barlow et al, 2006), and nucleobase cation radicals . Barlow et al showed that [arginine] þ. cation radicals produced by charge-transfer dissociation of [Cu (II) (terpy)(R)] 2þ were structurally different from the cation-radicals produced from [Fe (III) (Barlow et al, 2005(Barlow et al, , 2006.…”
Section: A Redox Reactions In Ternary Complexesmentioning
confidence: 99%
“…5 appears to represent a rare example in which CID is used to study the unimolecular chemistry of a mass-selected radical cation of a biomolecular dimer. An examination of the literature reveals only one other previous study, in which Ke et al probed the fragmentation reactions of mass-selected dimer radical cations of N-acetylated derivatives of the aromatic amino acids tryptophan and tyrosine, which were also formed via redox reactions of copper complexes [35]. They also observed the competition between formation of the monomer radical cation (cf.…”
Section: Fragmentation Reactions Of the Nucleoside Homodimeric And Hementioning
confidence: 99%